Load dependent friction coefficient of crystalline graphite and anomalous behavior of wear dimension. (August 2015) - Kumar, N.; Kozakov, A.T.; Ravindran, T.R.; Dash, S.; Tyagi, A.K.
Abstract: Load dependent friction behavior of crystalline graphite was studied under ambient atmospheric condition. Structural disorder in the wear track of graphite is increased with load as investigated by micro-Raman spectroscopy. At low loading range, the chemical structure of graphite does not change much and structure remains in 3D graphite phase although there is increase in friction coefficient. This is explained by increase in wear dimension which is directly related to frictional energy. However, wear dimension remains unchanged at high loading range but friction coefficient consistently increases. This is related to transformation of 3D graphite into 2D structure at high loading ranges which consists of highly disordered state of lattice resulting increase in friction coefficient. Graphical abstract: Highlights: A load dependent tribological property of crystalline graphite is investigated. Friction and wear behavior is correlated with structural order/disorder in graphite. Friction induced phase transformation in graphite is observed. Friction in graphite is increases with increase in loads due to lattice disordering.